GAMBARAN PENERAPAN HAND HYGIENE PADA MAHASISWA PROFESI NERS - Azizah, Azizah; Suci, Wice Purwani; Tampubolon, Masrina Munawarah (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Background: The incidence rate of HAIs (Healthcare-Assosiated Infection) is a benchmark for hospital services; if the HAI rate of a hospital is high, it can be interpreted that the quality of the hospital's services is poor. The spread of HAIs can occur even through non-invasive actions, such as physical contact between an infected patient and other patients or visitors, or with the hospital environment. The low level of compliance among healthcare workers in implementing hand hygiene can lead to an increase in the spread of HAIs in hospitals. Nursing students are personnel who often come into direct contact with patients, and the proper and correct implementation of hand hygiene is very important to reduce the spread of HAIs in hospitals. Objective: To determine how hand hygiene is applied among nursing profession students at Riau University. Methods: This research is a descriptive study with a quantitative approach. The sample in this study consisted of 128 respondents thats all are nursing profession students at Riau University using the total sampling method. Result: Out of 128 student respondents, the majority applied hand hygiene positively (56,25%). The application of hand hygiene at moment 1 was found to be 75,78% positive, at moment 2 it was 69,53% positive, at moment 3 it was 75% positive, at moment 4 it was 74,22% positive, at moment 5 it was 78,12% positive, and the application of hand hygiene using the 6-step hand hygiene method was found to be 71,87% positive. Conclusion: The nursing profession students at Universitas Riau have positively implemented hand hygiene. The application of hand hygiene among the nursing profession students at Universitas Riau is positive (56,25%) but still needs improvement. Keywords: hand hygiene, handwashing, nursing profession Abstrak Pendahuluan: Angka kejadian HAIs (Healthcare-Assosiated Infection) merupakan tolak ukur pelayanan rumah sakit, jika angka HAIs suatu rumah sakit itu tinggi, maka dapat diartikan pelayanan rumah sakit tersebut memiliki mutu yang buruk. Penyebaran HAIs dapat terjadi bahkan melalui tindakan non-invasif, yaitu dengan adanya kontak fisik antara pasien yang sedang terinfeksi dengan pasien lain atau pengunjung, ataupun dengan lingkungan rumah sakit. Tingkat kepatuhan petugas kesehatan yang masih rendah dalam penerapan hand hygiene dapat menyebabkan semakin tinggginya penyebaran HAIs di Rumah sakit. Mahasiswa profesi ners merupakan petugas yang sering berhadapan langsung dengan pasien, penerapan hand hygiene yang baik dan benar sangat penting untuk mengurangi angka penyeparan HAIs di rumah sakit. Tujuan: Mengetahui bagaimana penerapan hand hygiene pada mahasiswa profersi ners Universitas Riau. Metode: Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Sampel pada penelitian ini berjumlah 128 responden yang seluruhnya merupakan mahasiswa profesi ners Universitas Riau dengan metode sampling total sampling. Hasil: Dari 128 mahasiswa responden, didapatkan mayoritas responden menerapkan hand hygiene dengan positif (56,25%). Penerapan hand hygiene pada momen 1 didapatkan 75,78% positif, pada momen 2 didapatkan 69,53% positif, pada momen 3 didapatkan 75% positif, pada momen 4 didapatkan 74,22% positif, pada momen 5 78,12% positif, dan penerapan hand hygiene dengan menggunakan 6 langkah hand hygiene didpatkan 71,87% positif. Kesimpulan: Mahasiswa profesi ners Universitas Riau telah menerapkan hand hygiene dengan positif Penerapan hand hygiene pada mahasiswa profesi ners Universitas Riau positif namun masih perlu untuk ditingkatkan. Kata Kunci: kebersihan tangan, cuci tangan, profesi ners